1990
DOI: 10.1002/pssb.2221620135
|View full text |Cite
|
Sign up to set email alerts
|

Resonant Tunneling in a Symmetrical Rectangular Quadruple‐Barrier Structure

Abstract: The resonant tunneling phenomena in double-barrier structures have been studied both theoretically and experimentally by many researchers in these twenty years /1 to 7 1 . However, few theoretical studies have been made for the quadruple-barrier structure / 8 / . Especially, it seems that a study of the resonant tunneling for the symmetrical quadruple-barrier structure has not been carried out yet, though an interesting and useful feature for the resonant tunneling may be veiled. Actually, some interesting fea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1993
1993
2015
2015

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…It is confirmed that the variation of each resonance level is not so sensitive to changes of the outer barrier width L b l and is negligible, although the values of the transmission coefficient in the off-resonance energy range become smaller and the transmission spectrum becomes sharper with increasing outer barrier width. It leads to the result that the two independent resonance conditions (9) and (10) are almost retained even if the outer barrier width is not exactly equal to the inner one as in [9]. This result may be useful for new device fabrication.…”
Section: Tunneling Transmission Characteristicsmentioning
confidence: 84%
See 2 more Smart Citations
“…It is confirmed that the variation of each resonance level is not so sensitive to changes of the outer barrier width L b l and is negligible, although the values of the transmission coefficient in the off-resonance energy range become smaller and the transmission spectrum becomes sharper with increasing outer barrier width. It leads to the result that the two independent resonance conditions (9) and (10) are almost retained even if the outer barrier width is not exactly equal to the inner one as in [9]. This result may be useful for new device fabrication.…”
Section: Tunneling Transmission Characteristicsmentioning
confidence: 84%
“…For Lbl = Lbl, the probability density at the resonance energy obtained by the resonance condition (9) is invariant for various central well widths as shown Fig. 4b, because (9) gives the resonance condition for the double-barrier structure containing the outer well. It is seen for Lbl < Lba that the amplitude of the probability density is decreased as shown in Fig.…”
Section: Confining Phenomenamentioning
confidence: 96%
See 1 more Smart Citation
“…However, the well width decides definitely the resonance levels in the symmetrical triple-barrier as well as in the double-barrier structures: If one resonance level is selected, the other levels are decided according to the resonance condition with well width. On the other hand, the quadruple-barrier structures follow two independent resonance conditions and two independent resonance levels simultaneously [6].…”
Section: Introductionmentioning
confidence: 99%